The Correlation between Students’ Habits of Watching English Movies and Their Command of English Vocabulary - Kholifah, Nurul; Taufiq, Wahyu (Universitas Muhammadiyah Gresik, 2023)
The objective of the research is to know the correlation between the student’s habits of watching English movies and their command of English vocabulary. The researh was done in a senior high school in Sidoarjo, East Java, Indonesia. The purpose of this study is to know whether the students’ habits of watching English movies correlate with their command of English vocabulary. The instruments include questionnaires to invertigate the scale of students’ habits of watching movies and tests to measure the students’ command in English vocabulary. The result of the research concludes that there is a significant correlation between the habits of watching English movies and the vocabulary command, therefore the habits can be suggested as one of activities to be done out side of the class.